Rhetorics of self-making - Battaglia, Debbora (Berkeley : University of California Press, 1995)
This book advances the cross-cultural study of selfhood in three ways: First, it argues that selfhood is culturally situated and emergent in social practices of persuasion. Second, it demonstrates how postmodernity problematizes the experience and concept of the self. Finally, it challenges the pervasive practice of equating an individuated self with the Western world and a relational self with the non-Western world.
Problematizing the self: a thematic introduction / Debbora Battagli -- Self-exposure as theory: the double mark of the male Jew / Jonathan Boyarin and Daniel Boyari -- On eccentricity / George E. Marcu -- If you have the advertisement you don't need the product / Roy Wagne -- On practical nostalgia: self-prospecting among urban trobrianders / Debbora Battagli -- Nostalgia and the new genetics / Marilyn Strather -- Production values: indigenous media and the rhetoric of self-determination / Faye Ginsbur.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Self -- Social aspects; Self -- Cross-cultural studies; Ethnopsychology; Ethnopsychology; Moi (Psychologie) -- Aspect social; Moi (Psychologie) -- Études transculturelles; Ethnopsychologie; ethnopsychology; PSYCHOLOGY -- Personality; SOCIAL SCIENCE / Anthropology / Cultural & Social; Ethnopsychology; Self; Self -- Social aspects; Psychology; Social Sciences; Cross-cultural studies